Filsafat Ilmu: Dialektika Epistemologi, Ontologi, dan Aksiologi dalam Konteks Perubahan Sosial - Ardi Ansah Rambe; Sahrul Gunawan; Sonia Rusyanti; Nunu Mahnun (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to explore in depth the role of philosophy of science in understanding and responding to the dynamics of social change through conceptual interactions between epistemology, ontology, and axiology. Using qualitative methods and a philosophical-hermeneutic approach, this study examines classical and contemporary works of philosophy of science to reveal the meaning contained in the dialectic of these three dimensions. The results of the analysis show that epistemology functions as a foundation for acquiring and validating knowledge, ontology affirms that social reality is constructive and constantly undergoing reconstruction, while axiology provides direction for values and ethics so that knowledge does not lose its moral orientation. The interaction between epistemology, ontology, and axiology forms a dynamic dialectic resembling the Hegelian framework (thesis, antithesis, synthesis), resulting in a new understanding that is more reflective and transformative. This dialectic is an important foundation in formulating strategies for the development of science that are relevant to the needs of contemporary society. In addition to contributing theoretically to the enrichment of the study of the philosophy of science, this research also offers practical implications in the fields of education, public policy, and social development. Thus, the philosophy of science is not merely a theoretical reflection, but an intellectual compass that guides society to remain grounded in the integrity of knowledge, clarity of reality, and commitment to human values amid the tide of global transformation